Police Deployment—Introduction - Larson, Richard C. (Management Science, 1978)
Introduction to the special issue devoted to police deployment. By publishing these four refereed papers together in one issue of Management Science, we have the dual purpose of presenting new substantive research results in an important public sector problem area and of attracting other management scientists to the area. The field is still relatively new for OR/MS professionals, and much work remains to be done.